A structural UGDH variant associated with standard Munchkin cats - Ann-Kathrin Struck; Marina Braun; Kim Aline Detering; Peter Dziallas; Jasmin Neßler; Michael Fehr; Julia Metzger; Ottmar Distl (BMC Genetics, 2020)
Abstract Background Munchkin cats were founded on a naturally occurring mutation segregating into long-legged and short-legged types. Short-legged cats showed disproportionate dwarfism (chondrodysplasia) in which all four legs are short and are referred as standard Munchkin cats. Long-legged animals are referred as non-standard Munchkin cats. A previous study using genome-wide single nucleotide polymorphisms (SNPs) for genome-wide association analysis identified a significantly associated region at 168–184 Mb on feline chromosome (FCA) B1. Results In this study, we validated the critical region on FCA B1 using a case-control study with 89 cats and 14 FCA B1-SNPs. A structural variant within UGDH (NC_018726.2:g.173294289_173297592delins108, Felis catus 8.0, equivalent to NC_018726.3:g.174882895_174886198delins108, Felis catus 9.0) on FCA B1 was perfectly associated with the phenotype of short-legged standard Munchkin cats. Conclusion This UGDH structural variant very likely causes the chondrodysplastic (standard) phenotype in Munchkin cats. The lack of homozygous mutant phenotypes and reduced litter sizes in standard Munchkin cats suggest an autosomal recessive lethal trait in the homozygote state. We propose an autosomal dominant mode of inheritance for the chondrodysplastic condition in Munchkin cats.